1995
DOI: 10.1107/s0108768195005465
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of waxes

Abstract: Quantitative electron crystallographic studies have been carried out on epitaxially oriented multi-component waxes. Intensities from two paraffin-based samples, an artificial six-component medium wax (equimolar distribution of chain lengths) and a petroleum-based wax (Gaussian distribution of chain lengths) have been used to determine their crystal structures. As found earlier for binary paraffin solid solutions, differences in molecular volume are compensated by longitudinal molecular shifts within individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 22 publications
(36 reference statements)
3
72
0
1
Order By: Relevance
“…Edwards [11] studied the crystal habit of paraffin wax. Dorset [12,13] demonstrated that beeswax had a disordered lamellar interface. Although PLM does not provide quantitative and definitive comparison among materials from different sources and with a wide melting range, it does give a …”
Section: Observation Of Wax Crystallines By Polarized Light Microscopmentioning
confidence: 99%
“…Edwards [11] studied the crystal habit of paraffin wax. Dorset [12,13] demonstrated that beeswax had a disordered lamellar interface. Although PLM does not provide quantitative and definitive comparison among materials from different sources and with a wide melting range, it does give a …”
Section: Observation Of Wax Crystallines By Polarized Light Microscopmentioning
confidence: 99%
“…1-3 Recent crystallographic investigations 4 have shown that the structure of multicomponent solid solutions is very similar to the simpler cosoluble binary solids. 5,6 (That is to say, there is a single lamellar thickness with a fractional occupancy of atoms at molecular ends to account for the statistical distribution of two or more chain lengths in an average mixed lamella.)…”
Section: Introductionmentioning
confidence: 98%
“…A series of higher order (00l)-reflections indicates a regular, periodic structure and represents the periodical sequence of electronic density differences in multiple layers. In the case of hydrocarbons, such as alkanes, the series of (00l)-peaks originates from the region of lower scattering density in the gap between the molecular layers [17,18]. The acyl chains of the α-polymorph do not form an angle of tilt; whereas those of β'-and β-polymorphs form an angle of tilt between 50° and 70° [19,20].…”
Section: X-ray Data Analysis and Polymorphism Of Jlesmentioning
confidence: 99%